Effect of cantilever length on stress distribution around implants in overdentures supported by two implants - Ramin Mosharraf; Behnaz Ebadian; Nilofar Khodaeian (Isfahan University of Medical Sciences, 2011)
Introduction: Reducing stress on implats in overdentures supported by two implants via optimal stress distribution is nessecery. The aim of this study was to evaluate stress distribution pattern around implants in overdentures supported by two impalnts with varying cantilever lengths using finite element analysis.Materials and Methods: The model used in this experimental-analytical study was an implant-supported overdenture with bar and clip attachment system on an edentulous mandibular arch. Two vertical impalnts with cantilever lengths of 0 mm, 7 mm, and 13 mm were connected by a bar. Vertical loads of 15 and 30 pounds were applied unilaterally to the first molar and 15 pounds to the first premolar; the stress in bone was analyzed by finite element method.Results: In the 7-mm and 13-mm cantilever models loaded by 15 Ib on the molar area, the stress values around the implants were 2.78 and 2.75 MP, respectively, compared to 3.06 MP in the model without cantilever. By loading a 30-Ib force in the molar area, stress values around the implants were 6.9, 6.42 and 6.28 MP in no cantilever, 7-mm and 13-mm cantilever models, respectively. No uniform pattern of stress distribution was seen by increasing the cantilever length; however, increasing cantilever length did not increase stress around the ipsilaleral implant.Conclusion: Within the limitations of this study, increasing cantilever length did not increase stress values, especially around the ipsilateral implants and it may be helpful to use cantilevers in cases of mandibular overdentures supported by splinted implants with insufficient retention and stability. Based on the findings of this study, optimal cantilever length in mandibular overdentures cannot be determined. Key words: Biomechanics, Computerized simulation, Dental implant, Finite element analysis, Overdenture, Stress analysis methods.